Unconsumed Food Concerns: the Case of the United Arab Emirates - Florkowski, Wojciech J. (2023)
The article identifies factors influencing consumer attitudes with regard to unconsumed food in the wealthy economy of the United Arab Emirates (UAE), where the vast majority of the population are transient residents. The estimated regression coefficients were used to calculate the marginal effects, which measure change in probability of attitude towards the unconsumed food. The study applied the survey data collected from 1,542 UAE residents. The respondents included individuals representing 70 nationalities – transient residents of the UAE, mostly Filipinos (26%) and citizens of India (20%), and the UAE nationals (11%). Results show that persons showing most frequently concern about unconsumed food are women, older, college educated, and high income. Additionally, those concerned were also the long-term residents of the UAE as well as the supporters of investment in renewable energy. The sole factor that was associated with lower probability of being concerned about unconsumed food was the number of owned cars (on average 2.7 cars per household).